Submental intubation in cases of panfacial fractures: A retrospective study - Rodrigues, Willian Caetano [UNESP]; De Melo, Willian Morais [UNESP]; De Almeida, Rafael Santiago [UNESP]; Pardo-Kaba, Shajadi Carlos; Sonoda, Celso Koogi [UNESP]; Shinohara, Elio Hitoshi [UNESP] (American Dental Society of Anesthesiology (ADSA), 2017)
Surgical treatment of panfacial fractures usually requires intraoperative temporary occlusion of the teeth and simultaneous access to the nasal pyramid. In such cases, the standard method of airway management is to perform a tracheostomy, but this may be associated with a significant number of perioperative and late complications. This study aimed to determine if submental endotracheal intubation (SEI) is a viable alternative to tracheostomy, especially when short-term postoperative control of the airway is foreseen. This was an observational retrospective study, carried out between 2012 and 2014, which involved 32 consecutive patients who sustained panfacial fractures and were surgically treated during a 3-year period in a level I trauma center hospital. Only those who required SEI were included in the sample. Four cases were excluded because of incomplete registries, follow-up period less than 4 months after hospital discharge, or other unrelated complications. The medical charts of all patients involved in the sample were carefully reviewed in order to qualify and quantify perioperative and postoperative complications related to anesthetic management. We hypothesized that SEI would not interfere with the surgical procedures and would present less morbidity and reduced complication rates. Twenty-eight patients, 24 male and 4 female, met all the inclusion criteria. The mean age was 29.5 ± 9.05 years (range, 18-56 years). The mean duration time of surgery was 8.07 ± 4.0 hours (range, 4-16 hours). There were no perioperative complications. Postoperatively, only 1 patient (3.57%) experienced a cutaneous infection at the submental region, which was easily treated. Additionally, only 1 case (3.57%) of hypertrophic scar was reported. SEI appears to be a safe, simple, and effective technique of immediate perioperative airway management in selected cases of panfacial fractures.
Keywords: Airway management; Intubation; Maxillofacial trauma; Submental